Rancangan Strategi Pemasaran Media Sosial Menggunakan Model SOSTAC - Yoga Aditya Pranata; Reni Amaranti (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. PT. X is a manufacturer of motorcycle accessories and parts. The company's social media is currently not optimal and left behind by competitors so that product sales do not reach the marketing target of brand awareness for SND Racing products, considering that social media is the marketing and promotion channel with the most users on the internet. This study aims to design a social media marketing strategy to increase brand awareness of SND Racing products with the scope of research from September 2012 to February 2021. The design of social media marketing strategies is carried out on the Facebook and Instagram platforms using the SOSTAC model. The performance of the social media marketing strategy design as measured using Keyhole.co analytics to find out the most frequent post types, the most interesting post types, optimal delivery times, best delivery times, optimal post lengths, hashtags based on interactions, and optimal hashtags to use as the basis for the proposal effective social media marketing strategy design. social media marketing strategy can provide a significant difference in increasing brand awareness compared to the previous year, as evidenced by the Wilcoxon signed-rank test hypothesis because H0 is rejected (Tcount (1) > Ttable (0)). Abstrak. PT. X merupakan produsen aksesoris dan onderdil motor. Pemasaran media sosial perusahaan saat ini belum optimal dan tertinggal oleh kompetitor sehingga penjualan produk tidak mencapai target dikarenakan kesadaran merek untuk produk SND Racing masih rendah mengingat media sosial adalah saluran pemasaran dan promosi dengan pengguna terbanyak di internet. Penelitian ini bertujuan untuk merancang strategi pemasaran media sosial untuk meningkatkan kesadaran merek produk SND Racing dengan ruang lingkup penelitian pada bulan September 20120 sampai bulan Februari 2021. Perancangan strategi pemasaran media sosial dilakukan pada platform Facebook dan Instagram menggunakan model SOSTAC. Performa rancangan strategi pemasaran media sosial diukur menggunakan analitik Keyhole.co untuk mengetahui tipe kiriman paling sering, tipe kiriman paling menarik, waktu kirim optimal, waktu kirim terbaik, panjang kiriman optimal, tagar teratas berdasarkan keterlibatan, dan tagar optimal yang akan digunakan sebagai dasar usulan rancangan strategi pemasaran media sosial efektif. Rancangan strategi pemasaran media sosial dapat memberikan perbedaan signifikan terhadap peningkatan kesadaran merek dibandingkan tahun sebelumnya, dibuktikan oleh uji hipotesis Wilcoxon signed-rank test dikarenakan H0 ditolak (Thitung (1) > Ttabel (0)).